Evaluation of the Expression of the Human Epithelial Receptor 2 (HER2) in Gastric Carcinoma - Roberto de Moraes Cordts Filho; Paulo Kassab; Laura Carolina Lopez Claro; Mabel Tatty de Medeiros Fracassi; Patrícia Colombo-Souza; Daniel Kenji Fukuhara; Fábio Rodrigues Thuler; Wilson Rodrigues de Freitas Junior; Elias Jirjoss Ilias; Carlos Alberto Malheiros (The Scientific World Journal)
Objective. To evaluate the HER2 expression on gastric adenocarcinoma from a Brazilian population and also to analyze the relations between the receptor and clinical characteristics, as well as the survival status. Materials and Methods. A retrospective analysis was conducted from January of 2008 to July of 2012, considering only gastrectomies with curative intent. Tumors were tested for HER2 status using immunohistochemistry. The relation between HER2 status and clinical aspects, surgical findings, and survival were also analyzed. Results. 222 patients with gastric carcinoma were submitted to surgery during that period, but only 121 (54,5%) were with curative intention. The immunohistochemistry revealed that 4 patients (3,3%) were HER2-positive, 6 patients (4,9%) HER2-undetermined, and 111 patients (91,7%) HER2-negative. There was no statistical concordance between HER2 status and survival or the clinical aspects. Conclusion. The HER2 overexpression rate was very low in this Brazilian population sample and cannot be considered as a prognostic factor.